2018
DOI: 10.1371/journal.pone.0197934
|View full text |Cite
|
Sign up to set email alerts
|

Propofol elicits autophagy via endoplasmic reticulum stress and calcium exchange in C2C12 myoblast cell line

Abstract: In this study, we investigated the relationship between propofol and autophagy and examined whether this relationship depends on ER stress, production of ROS (reactive oxygen species), and disruption of calcium (Ca2+) homeostasis. To this end, we measured C2C12 cell apoptosis in vitro, along with Ca2+ levels; ROS production; and expression of proteins and genes associated with autophagy, Ca2+ homeostasis, and ER stress, including LC3 (microtubule-associate protein 1 light chain 3), p62, AMPK (adenosine 5’-mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Besides, the generation of intracellular ROS could induce oxidative damage, and DCFH-DA is generally used to measure ROS generation in cells [24]. The fluorescence images showed that there was a visible increase of the fluorescence staining of ROS (green) in the CMs after treating the high dose of four compounds, the same as statistical results of fluorescence density as shown in Fig.…”
Section: Resultssupporting
confidence: 52%
“…Besides, the generation of intracellular ROS could induce oxidative damage, and DCFH-DA is generally used to measure ROS generation in cells [24]. The fluorescence images showed that there was a visible increase of the fluorescence staining of ROS (green) in the CMs after treating the high dose of four compounds, the same as statistical results of fluorescence density as shown in Fig.…”
Section: Resultssupporting
confidence: 52%
“…In future, these molecules may be proposed as an antitumor metabolic agent in clinical settings. 70 In a multi-omic study, Myc gene expression was found to be strongly associated with metabolic reprogramming in adenoma to carcinoma sequence. It regulates the genes involved in mitochondrial biogenesis hence molecules targeting Myc expression could be a potential target for cancer therapy.…”
Section: Treatment Strategies Based On Cms Subtypes Of Colorectal Cancermentioning
confidence: 99%
“…Propofol exerts an organ protective effect by modulating ER stress, although patterns of ER stress changes vary. Chen et al [ 18 ] revealed that propofol enhanced ER stress and ultimately induced cell apoptosis of unnecessary muscle tissue to protect muscle. By contrast, Wang et al [ 19 ] observed a neuroprotective effect of propofol through a reduction of ER stress and amelioration of neuronal cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%